Variability of PCB burden in 5 fish and sharks species of the French Mediterranean continental slope. (May 2016) - Cresson, Pierre; Fabri, Marie Claire; Miralles, Françoise Marco; Dufour, Jean-Louis; Elleboode, Romain; Sevin, Karine; Mahé, Kelig; Bouchoucha, Marc
Abstract: Despite being generally located far from contamination sources, deep marine ecosystems are impacted by chemicals like PCB. The PCB contamination in five fish and shark species collected in the continental slope of the Gulf of Lions (NW Mediterranean Sea) was measured, with a special focus on intra- and interspecific variability and on the driving factors. Significant differences occurred between species. Higher values were measured in Scyliorhinus canicula, Galeus melastomus and Helicolenus dactylopterus and lower values in Phycis blennoides and Lepidorhombus boscii . These differences might be explained by specific abilities to accumulate and eliminate contaminant, mostly through cytochrome P450 pathway. Interindividual variation was also high and no correlation was observed between contamination and length, age or trophic level. Despite its major importance, actual bioaccumulation of PCB in deep fish is not as documented as in other marine ecosystems, calling for a better assessment of the factors driving individual bioaccumulation mechanisms and originating high variability in PCB contamination. Graphical abstract: Highlights: PCB concentrations were measured in 5 deep Mediterranean fish and shark species. Sharks and blackbelly rosefish had higher PCB values than megrim and forkbeard. These differences are consistent with specific contaminant absorption and excretion. Age, length and trophic position poorly explained PCB contamination. Actual effect of these factors should be better assessed for deep species. Abstract : PCB concentrations were different between 5 deep Mediterranean fish and sharks species. These differences were explained by specific abilities to accumulate and eliminate contaminant.